The McGill University Health Centre Cancer Pain Clinic: A Retrospective Analysis of an Interdisciplinary Approach to Cancer Pain Management - Jordi Perez; Sara Olivier; Emmanouil Rampakakis; Manuel Borod; Yoram Shir (Pain Research and Management)
Context. The McGill University Health Center (MUHC) Cancer Pain Clinic offers an interdisciplinary approach to cancer pain management for patients. The core team includes a nurse clinician specialist in oncology and palliative care, a palliativist, an anaesthetist, and a radiation oncologist. This tailored approach includes pharmacological and nonpharmacological therapies offered concurrently in an interdisciplinary fashion. Objectives. Description of the interdisciplinary MUHC cancer pain approach and analysis of treatments and outcomes. Methods. A retrospective analysis of new outpatients completing two subsequent visits (baseline and follow-ups: FU1, FU2) was conducted. Variables included (a) symptom severity measured by the Edmonton Symptom Assessment Scale, (b) pain and disability measured with the Brief Pain Inventory, and (c) analgesic plan implementation including pharmacological and nonpharmacological therapies. Results. 71 charts were reviewed. Significant pain relief was achieved consistently at FU1 and FU2. The average pain severity decreased by 2 points between initial assessment and FU2. More than half (53%) of patients responded with a pain reduction greater than 30%. Severity of other symptoms (i.e., fatigue, nausea, depression, and anxiety) and disability also decreased significantly at FU2. The total consumption of opioids remained stable; however, the consumption of short acting preparations decreased by 52% whereas the prescription of nonopioid agents increased. Beyond drug management, 60% of patients received other analgesic therapies, being the most common interventional pain procedures and psychosocial approaches. Conclusion. The MUHC interdisciplinary approach to cancer pain management provides meaningful relief of pain and other cancer-related symptoms and decreases patients’ disability.